1987
DOI: 10.1557/jmr.1987.0494
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural evolution in sintering of ALOOH gels

Abstract: Materials derived by precipitation or polymerization chemistry (e.g., “sol-gel” methods) are usually obtained in noncrystalline or otherwise metastable phases, and transformation to more thermodynamically stable phases generally occurs by a nucleation and growth process. In a fully reconstructive transformation, such as occurs in the alumina system, the activation energy for nucleation may be higher than that for simple short-range diffusion. Hence nucleation frequency can be a controlling factor in the develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 21 publications
1
24
0
Order By: Relevance
“…The typical grain growth features of a-Al 2 O 3 obtained from calcination of boehmite or heating of c-Al 2 O 3 reported by other studies are confirmed [9][10][11][12].…”
supporting
confidence: 76%
See 1 more Smart Citation
“…The typical grain growth features of a-Al 2 O 3 obtained from calcination of boehmite or heating of c-Al 2 O 3 reported by other studies are confirmed [9][10][11][12].…”
supporting
confidence: 76%
“…The formation of a single-crystal vermicular microstructure is difficult to understand as these grains consist of sub-units of similar size and with the same crystal orientation on both sides of the mutual necking. It has been proposed that a-Al 2 O 3 nucleation from h-phase was sporadic rather than uniform, leading to exaggerated grain growth and vermicular microstructure [10]. Others speculate that the phase transformation from boehmite might not proceed by a single-crystal to single-crystal transition [11].…”
mentioning
confidence: 99%
“…Underneath the diamond peak there is a band that can be assigned to the D band of graphitic carbon, 36,37 which is located at 1357 cm Ϫ1 . 36,38 The band is strongest for the 80 and 100 sccm samples, which may be caused by the very strong secondary nucleation on the crystallites of these samples. 37 As follows from the overlay of the spectra in Fig.…”
Section: Raman Spectroscopymentioning
confidence: 95%
“…The reason for the occurrence of this transformation at such a low temperature may be the contribution of sol -gel byproducts of aluminium nitrate in the gel 17 and the seeding effect of the fine KTiO whiskers. 18 Figure 3 shows the TEM morphology of the sol -gel processed a-Al 2 O 3 coating on the whisker surfaces. It can be seen that a dense alumina coating was uniformly deposited on the whisker surfaces.…”
Section: Methodsmentioning
confidence: 99%